(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study investigates the gap in current research regarding the spread of linguistic innovations on social media platforms and highlights the need for this study to understand language dynamics in digital communication. Research objectives consist of analyzing how neologisms and linguistic borrowings spread on social media and exploring the role of hashtags, memes, and other internet linguistic elements in language evolution. The significance of the study is associated with the implications for linguistics, sociolinguistics, and digital communication, as well as potential contributions to the understanding of language trends in a global context.